LITERASI DAN EDUKASI PAJAK DALAM MENDORONG KEPATUHAN WAJIB PAJAK UMKM DI KARTASURA - Fitri Handayani; Dewi Purnasari; Reni Febriani; Muhammad Ismail; Sofia Ningsih Rahayu Putri (ITB AAS Indonesia, 2026)
This study aims to analyze the role of tax literacy and education in encouraging taxpayer compliance among Micro, Small, and Medium Enterprises (UMKM) in Kartasura District. In the context of local economic growth, tax compliance is a crucial factor in supporting regional revenue. However, UMKM contribution to taxation is hampered by low levels of tax literacy and minimal education for UMKM. This often becomes a major obstacle in fulfilling tax obligations. This study used a quantitative approach by distributing questionnaires to UMKM in the Kartasura area as respondents. The results indicate that good tax literacy and appropriate education have a positive and significant impact on taxpayer compliance levels. This demonstrates the important role of the government and relevant agencies in improving tax understanding through ongoing education programs and communication strategies that are easily understood by UMKM. Therefore, in the future, it will result in a conclusion, improving tax literacy and education is an effective strategy in encouraging tax compliance among UMKM in Kartasura.